Nativity of the Virgin Mary Kozelshchynskyi Monastery in the Poltava Region: an assessment of architectural heritage and contemporary challenges - Osychenko, Halyna; Khliupin, Oleksandr (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The challenge of preserving the architectural heritage of small towns in Ukraine is compounded by the lack of sufficient historical and architectural research, as well as numerous alterations to buildings during their use. This article presents the results of historical and architectural research on the architectural heritage of the Nativity of the Virgin Mary Kozelshchyna Monastery in the Poltava Region. It explores the historical stages of the monastery’s formation and development and evaluates its historical and cultural significance. A virtual reconstruction of the monastery’s original appearance was undertaken, and the historical boundaries of the monastery were established. The analysis of the current state enabled the identification of issues related to the monastery’s functioning and the preservation of its cultural heritage. This research provides a scientific foundation for developing protection zones for the monastery and for restoration and adaptation projects of its buildings. It also establishes an information base for future project work and the monitoring of architectural heritage.